PENINGKATAN PERFORMA TURBIN ANGIN SUMBU HORISONTAL BERSUDU AIR FOIL MELALUI PENAMBAHAN NOSEL DAN DIFUSER - Jhon A. Wabang; Agustinus Betan; Edwin Hattu; Ambros Tuati; Thomas Fongo; Piter Tukah (ROTOR, 2016)
Horizontal axis wind turbine air foil blade is one of several types of wind turbines to convert the kinetic energy in wind into mechanical energy of the wind turbine. Mechanical energy wind turbine is then converted into electrical energy through a generator and also for irrigation and other functions. The mechanism of utilization of wind energy to generate electricity or irrigation function is a positive step because the kinetic energy of wind is the energy that is environmentally friendly, does not cause air pollution, on the other hand, wind energy freely available in nature. In this research, the process of converting the kinetic energy of wind into mechanical energy through a horizontal axis wind turbine air foil blade is still done on a laboratory scale. The purpose of this study was to determine the torque and power of horizontal axis wind turbines air foil blade. The method of implementation of this research is a horizontal axis wind turbine air foil blade in the test using a fan with three speeds varying found on the fan. The wind turbine is also tested using additional devices such as utilization of nozzle and diffuser to determine the performance of the turbine. The addition nozzle and diffuser is a method of increasing the efficiency of wind turbines because look at the function of the nozzle and diffuser itself. Dimensions of wind turbines in the study had a sweep of the area of 50 cm2 and the number of blades used 3 pieces or blades. The mechanism of this device test carried out in three stages, namely testing without using nozzle and diffuser, using a nozzle testing and testing using a diffuser. From the experimental results, it can be concluded that the first speed, the greatest torque and power the of the wind turbine without nozzle and diffuser is 0.1017 Nm and 4,126 W; at a speed of 2, the greatest power and torque occurs in the turbine using a diffuser that is 0.1195 Nm and 6.88 W; at 3 speed, torque and power are greatest in the turbine using a diffuser that is 0.1166 Nm and 7,935 W. Keywords: Wind turbine, Airfoil, Nozzle, Diffuser.